EFFECT OF DIFFERENT SEED TREATMENT ON DRAGON FRUIT (Hylocereus undatus Hylocereus undatus Britt. & Rose) SEED GERMINATION AND SEEDLING GROWTH - SANDESH, H. J.; G. S. K. , SWAMY (The Bioscan, 2018)
An investigation was carried out to determine the most suitable seed treatment for better germination and establishment of healthy dragon fruit seedlings. Freshly extracted dragon fruit seeds were subjected to different seed treatments viz., hydrochloric acid (HCL) quick dip for 5 seconds (T1), GA3 500 ppm for 12 hours (T2), Water soaking for 12 hours (T3), Thiourea at 1% for 12 hours (T4), GA3 250 ppm for 12 hours (T5), KNO3 at 1%for 12 hours (T6), quick dip in hot water for 5 seconds (T7) and Control with three replications. The results revealed that seeds treated with 500 ppm of GA3 gave early germination (4.66 days), highest germination percentage (100.00%), survivability percentage (88.46%), vigour index (333.00) and vegetative growth parameters like number of roots (3.66), longest length of roots (1.55cm), shoot length (1.78cm), seedling height at 90 DAT (20.23 cm), number of sprouts at 90 DAT (8.66) and longest sprout length (13.73 cm). The results suggest that seed treatment with GA3 500 ppm is found to be better in germination and seedling growth